2019
DOI: 10.1002/glia.23719
|View full text |Cite
|
Sign up to set email alerts
|

P2Y13 receptors regulate microglial morphology, surveillance, and resting levels of interleukin 1β release

Abstract: Microglia sense their environment using an array of membrane receptors. While P2Y12 receptors are known to play a key role in targeting directed motility of microglial processes to sites of damage where ATP/ADP is released, little is known about the role of P2Y13, which transcriptome data suggest is the second most expressed neurotransmitter receptor in microglia. We show that, in patch‐clamp recordings in acute brain slices from mice lacking P2Y13 receptors, the THIK‐1 K+ current density evoked by ADP activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 66 publications
0
41
0
Order By: Relevance
“…In order to address whether this pathway was required for microglia-node contact, we first inhibited the P2Y12R receptor specifically using PSB0739 (1 μM), a highly potent P2Y12 antagonist, and found that it is not required for microglia-node interaction (15.1 ± 1.2% of nodes contacted in control vs 15.5 ± 1.7% following treatment, Figure S4C-D). To further assess the potential role of the P2Y receptor family and exclude any compensatory mechanisms, we also inhibited P2Y13R, which participates in microglia dynamics control 39 , concomitantly to P2Y12R by using the MRS2211 inhibitor (50 μM). Again, there was no significant variation in the number of nodes contacted in control vs treated slices (15.1 ± 1.5% vs 14.3 ± 1.3% respectively, Figure S4E-F), confirming that P2Y12R and P2Y13R are not required for microglia-node interactions in physiological condition.…”
Section: Resultsmentioning
confidence: 99%
“…In order to address whether this pathway was required for microglia-node contact, we first inhibited the P2Y12R receptor specifically using PSB0739 (1 μM), a highly potent P2Y12 antagonist, and found that it is not required for microglia-node interaction (15.1 ± 1.2% of nodes contacted in control vs 15.5 ± 1.7% following treatment, Figure S4C-D). To further assess the potential role of the P2Y receptor family and exclude any compensatory mechanisms, we also inhibited P2Y13R, which participates in microglia dynamics control 39 , concomitantly to P2Y12R by using the MRS2211 inhibitor (50 μM). Again, there was no significant variation in the number of nodes contacted in control vs treated slices (15.1 ± 1.5% vs 14.3 ± 1.3% respectively, Figure S4E-F), confirming that P2Y12R and P2Y13R are not required for microglia-node interactions in physiological condition.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the deletion of P2Y12 may result in compensatory changes in P2Y13 as it is similarly highly expressed in microglia and may have similar functions. However, the inverse deletion of P2Y13 does not result in altered P2Y12 expression nor compensatory functioning in the brain [ 31 ], suggesting that these two similar receptors are independently regulated.…”
Section: Discussionmentioning
confidence: 99%
“…These receptors are preferentially activated by ATP and induce cation currents. Microglia also express four of the eight metabotropic P2Y receptors: P2Y1, P2Y6, P2Y12, and P2Y13 (Butovsky et al, 2014; Fukumoto et al, 2019; Koizumi et al, 2007; Kyrargyri et al, 2020). P2Y receptors have unique affinity profiles for different purine signals and are coupled to either Gq (P2Y1 and P2Y6) or Gi/o (P2Y12 and P2Y13) signaling cascades.…”
Section: Microglia Sense and Regulate Neuronal Hyperactivitymentioning
confidence: 99%